New models for geoscience higher education in West Africa - (:unkn) unknown (My University, 2018)
The challenges facing government-funded higher education institutions in West Africa in response to the demand for mineral resources require a spectrum of responses aligned with the multinational development programs. Efforts to meet the demands of industry and government organisations for skilled staff are undermined by the large numbers of students attracted to Earth Science courses in Africa. The African Union's African Mining Vision, the UN's Sustainable Development Goals and the New Education Model for Africa provide a framework for progress, however, there are only a few concrete examples that allow us to explore the strengths and limitations of different approaches. Two proactive initiatives based on locally-identified needs and that involve local and international collaborations are presented that allow such an analysis. The first, a public-private partnership entitled the West African Exploration Initiative (WAXI), provides graduate and professional training as a result of direct industry and partner government financial and in-kind support. The second initiative known as GEOLOOC is a new online training program supported by UNESCO and the International Mining for Development Centre that unites several West African universities in creating a common resource pool of Earth Science training materials. These activities are being carried out in collaboration with the local universities, and a new professional training centre based in Ouagadougou, Burkina Faso. In West Africa, by addressing locally-identified gaps in higher education delivery and by building local and international collaborations, the projects described here are starting to successfully implement new models to contribute to the enhancement of geoscience higher education. These new models complement existing government-funded Higher Education systems by providing them with much-needed support at a time of rapid change.
Keywords: African Research